Effects of Corporate Governance on Financial Performance of Firms in Nigeria - Ogunmokunwa, Adejoro Joshua; Mokuolu, Joseph Oluseye (Journal of Business Management and Economic Development, 2026)
This study examined the effects of corporate governance on financial performance of companies in Nigeria. The study used both cross-sectional and time series data extracted from financial reports of six (6) conglomerate industries from 2017 to 2023. The study employed descriptive, correlation and panel estimation techniques. Thereafter, Hausman test was conducted to know which of the model between fixed and random could be relied on for prediction. The result of the Hausman test indicated that random effect model is more reliable and the outcome showed that board composition and audit committee exhibited an insignificant negative relationship on financial performance of firms in Nigeria, gender diversity showed a positive but insignificant effect while the effect of board size is significant and positively related to financial performance of firms in Nigeria. Based on the results, the study suggested expanding the size (membership) of the board while adhering to the highest number permitted by the company's corporate governance rules. Businesses should make an effort to guarantee that board members are independent, meaning that they are not hired by the company in any capacity.